Respuesta :
1 bag = $2
3 bags = $5
9 bags = $36
we know someone unknown number of bags were sold
i'll represent those with a and b
a = number of 1 pound bags
b = number of 3 pound bags
2a + 5b = 36 ----- amount of money -(1)
a + b = 9 ------number of bags -(2)
from the second equation we have:
a = 9 - b
b = 9 - a
I'll use substitution method:
you could substitute either a or b into the equation (2)
I'll just use a
2a + 5b = 36
a = 9 - b
2(9 - b) + 5b = 36
18 - 2b + 5b = 36
-2b + 5b = 36 - 18
3b = 18
b = 6
no we know b = 6
we and to find a, we know that a = 9 - b
therefore a = 9 - 6
a = 3
the question only asked for the number of three pounds
which is represented here by b
therefore the answer of 3 pound bags is 6
3 bags = $5
9 bags = $36
we know someone unknown number of bags were sold
i'll represent those with a and b
a = number of 1 pound bags
b = number of 3 pound bags
2a + 5b = 36 ----- amount of money -(1)
a + b = 9 ------number of bags -(2)
from the second equation we have:
a = 9 - b
b = 9 - a
I'll use substitution method:
you could substitute either a or b into the equation (2)
I'll just use a
2a + 5b = 36
a = 9 - b
2(9 - b) + 5b = 36
18 - 2b + 5b = 36
-2b + 5b = 36 - 18
3b = 18
b = 6
no we know b = 6
we and to find a, we know that a = 9 - b
therefore a = 9 - 6
a = 3
the question only asked for the number of three pounds
which is represented here by b
therefore the answer of 3 pound bags is 6
Answer:
6
Step-by-step explanation:
Let c represent three-pound bags and a represent one-pound bags.
Use a system of equations:
{9 = c + a
{36 = 5c + 2a
−⅕[36 = 5c + 2a]
{9 = c + a
{−7⅕ = −c - ⅖a >> New Equation
____________
1⅘ = ⅗a
__ ___
⅗ ⅗
[tex]3 = a[/tex] [Plug this back into both equations above to get the c-term of 6]; [tex]6 = c[/tex]
I am joyous to assist you anytime.